2023
DOI: 10.3390/antibiotics12040650
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of ATP Synthase as New Antibacterial Candidates

Abstract: ATP, the power of all cellular functions, is constantly used and produced by cells. The enzyme called ATP synthase is the energy factory in all cells, which produces ATP by adding inorganic phosphate (Pi) to ADP. It is found in the inner, thylakoid and plasma membranes of mitochondria, chloroplasts and bacteria, respectively. Bacterial ATP synthases have been the subject of multiple studies for decades, since they can be genetically manipulated. With the emergence of antibiotic resistance, many combinations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Due to the different structures of ATP synthase between bacteria and mammalian [ 68 ], selectively targeting bacterial ATP synthase offers a safe and effective antibacterial approach that does not harm mammalian cells. Betaquiline is a successful ATP synthase inhibitor against multi-drug-resistant (MDR) and extensively drug-resistant (XDR) strains without causing toxic effects on ATP production in mammalian cells [ 20 , 69 ]. Developing ATP synthase inhibitors is therefore viewed as a promising potential solution to overcome drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the different structures of ATP synthase between bacteria and mammalian [ 68 ], selectively targeting bacterial ATP synthase offers a safe and effective antibacterial approach that does not harm mammalian cells. Betaquiline is a successful ATP synthase inhibitor against multi-drug-resistant (MDR) and extensively drug-resistant (XDR) strains without causing toxic effects on ATP production in mammalian cells [ 20 , 69 ]. Developing ATP synthase inhibitors is therefore viewed as a promising potential solution to overcome drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Affecting the energy metabolism process is another way for TCM to inhibit bacteria. Bacterial ATP synthase is a potential therapeutic target for developing a new solution to treat bacterial infections [ 20 ]. ATP synthase, also called F 0 F 1 ATP synthase, plays a vital role in cellular bioenergetics by facilitating the production of ATP from ADP and inorganic phosphate (Pi) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…ATP synthases, also known as F0F1-ATPases, are enzyme complexes that catalyze the synthesis of ATP from ADP and phosphate. 68,69 A previous study indicated that F0F1-ATPase is a promising target for the development of novel therapeutics for combating A. baumannii infections. Indeed, the F0F1-ATPase structure and function are largely conserved across bacteria, including Escherichia coli (the most studied model) and A. baumannii.…”
Section: ■ Discussionmentioning
confidence: 99%
“…All bacteria use ATP as their primary source of energy (Mackieh et al, 2023). ATP production differs significantly amongst bacteria.…”
Section: Oxidative Phosphorylation and Atp Productionmentioning
confidence: 99%